2000
DOI: 10.1103/physrevb.61.3699
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of a one-dimensional static spin modulation in insulatingLa1.95Sr0.05CuO

Abstract: We report the results of an extensive elastic neutron-scattering study of the incommensurate ͑IC͒ static spin correlations in La 1.95 Sr 0.05 CuO 4 , which is an insulating spin glass at low temperatures. Recent work by Wakimoto et al. has revealed the presence of new two-dimensional satellite peaks in La 1.95 Sr 0.05 CuO 4 at positions rotated by ϳ45°in reciprocal space from those found in superconducting samples. The present neutron-scattering experiments on the same xϭ0.05 crystal employ a narrower instrume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
175
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(205 citation statements)
references
References 29 publications
(53 reference statements)
27
175
3
Order By: Relevance
“…We observe a linear relationship δ ∼ x for x = 0.125, 0.025, and 0.035, which extrapolates back through zero at x = 0. This conclusion is somewhat different from that reached in previous studies of La 2−x Sr x CuO 4 , wherein a linear δ ∼ x relationship was also found for sufficiently large x, but δ was ∼ independent of x for very low concentrations < 0.02, which also displayed 3D C AF order 44,46 .…”
Section: B Time-of-flight Elastic Neutron Scattering Measurementscontrasting
confidence: 56%
“…We observe a linear relationship δ ∼ x for x = 0.125, 0.025, and 0.035, which extrapolates back through zero at x = 0. This conclusion is somewhat different from that reached in previous studies of La 2−x Sr x CuO 4 , wherein a linear δ ∼ x relationship was also found for sufficiently large x, but δ was ∼ independent of x for very low concentrations < 0.02, which also displayed 3D C AF order 44,46 .…”
Section: B Time-of-flight Elastic Neutron Scattering Measurementscontrasting
confidence: 56%
“…• Transition from Parallel to Diagonal SDW coincides with the appearance of superconductivity at x c ∼ 0.055 [24,27].…”
Section: Spatial Structures Of Spin In Lscomentioning
confidence: 99%
“…Wakimoto et al have employed a narrower instrumental Q resolution and succeeded in ascribing a certain magnetic peak to a certain twin; in a single twin, there exist only two satellites with the modulation vector along the orthorhombic b * axis as shown in Fig. 2(b) [24]. These works indicate that the SDW modulation is diagonal to the Cu-O-Cu axis for the x = 0.05 insulating sample, and suddenly turns to be parallel to the direction upon crossing the insulator-to-superconductor phase boundary at x c ∼ 0.055.…”
Section: Overview Of the Elastic Magnetic Peaks In Lscomentioning
confidence: 99%
“…6,7 On the theoretical side it was argued that ξ is finite due to topological defects that lead to frustration of the longrange spiral order. 12,13 Since the localization length is less than the magnetic scale, 1/κ < ξ, we expect that the effective description of transport properties, developed below in terms of the one-hole wave function, is quantitatively valid also at finite (small) doping (i.e.…”
Section: A Summary Of Previous Results and Notationmentioning
confidence: 99%
“…However for x < 1/8 and in Nd-free LSCO, charge order has not been detected, while IC magnetism persists down to x ≈ 0.02. 6,7 Thus while IC magnetic order is generically observed in the underdoped regime, static charge order seems to be confined to the neighborhood of x = 1/8. 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 000000000 Theoretically the IC magnetism in the cuprates is often modeled as originating from static charge stripes, and since these are not universally present, one is forced to introduce additional concepts, such as "fluctuating" stripes, electronic liquid crystals, etc.…”
Section: Introductionmentioning
confidence: 99%